Використання Docker для спрощення розробки та деплою застосунків - Косенко, М. А. (ХНУРЕ, 2025)
This article explores the role of Docker in modern application development and deployment. It discusses the advantages of containerization, the process of creating and managing containers, and the international regulatory frameworks that impact software deployment. The study highlights the importance of using standardized environments for development and ensures efficient, scalable, and portable application deployment.
Keywords: використання Docker; розробка деплою застосунків